Workplace violence from the ambulance personnel’s perspective, a qualitative study - Magnus Viking; Karin Hugelius; Erik Höglund; Lisa Kurland (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2026)
Abstract Background Despite increasing interest in the occurrence of workplace violence in ambulance services, few studies have explored the phenomenon from the perspective of the ambulance personnel. While previous studies have identified its incidence and risk factors, this study aimed to explore ambulance personnel’s understanding of why workplace violence occurs. Methods An inductive, qualitative study was conducted using digital focus group interviews. The inclusion criteria were as follows – having worked in ambulance services for a minimum of two years and having personally experienced workplace violence. Reflexive thematic analysis was employed in this study. Results Three focus group interviews with 10 Swedish ambulance personnel were included in the study. Three themes were identified: (I) ambulance personnel’s lack of competence and willingness to adapt can lead to workplace violence; (II) ambulance personnel’s inability to cope with their emotional response to provocation can lead to workplace violence; and (III) experiencing limited control in unpredictable situations. Workplace violence occurred when the ambulance personnel lacked empathy and compassion for the patient, acted disrespectfully, or when the power imbalance between ambulance personnel and the patient became apparent. If ambulance personnel felt provoked by the patient’s behaviour, it triggered workplace violence. Furthermore, if they could not read the situation and lost control of it or if the patient’s behaviour was unpredictable (e.g. if the patient was under the influence of drugs or alcohol), workplace violence ensued. Conclusions Ambulance personnel need to acknowledge their own contributions to the risk of workplace violence and identify situations and actions that could both increase and decrease the risk of exposure. Future studies should focus on implementing interventions to identify potential high-risk situations and train ambulance personnel to deescalate risky situations.